Analysis of Financing, Working Capital and Business Management in Improving Family Welfare in Kedai Durian Village - Cindy Alya Tantri; Muhammad Ikhsan Harahap; Muhammad Lathief Ilhamy Nasution (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aims to analyze the role of financing, working capital, and business management in improving family welfare in Kedai Durian Village. Using a descriptive qualitative approach, data were collected through in-depth interviews with 10 informants who are active BMT customers. The number of informants was determined based on data saturation, where no new themes emerged after the eighth interview. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results indicate that BMT financing significantly strengthened working capital, enabling inventory expansion, equipment purchase, and increased production capacity. Business management improvements measured through indicators such as financial record-keeping, stock planning, and customer service quality emerged organically as businesses grew. Family welfare improvements were multidimensional: economically, informants reported stable income enabling fulfillment of basic household needs, children's education, and savings; socially, business owners expanded community networks; and spiritually, all informants expressed inner peace from Sharia-compliant, interest-free financing aligned with Maqasid al-Shariah values. BMT financing thus functions as an integrated instrument of Islamic economic empowerment.